TRANSLATOR TRAINING IN TUNISIA TODAY: MARKET CHALLENGES AND AVAILABLE OPPORTUNITIES. - SALHI, Hammouda (Comparative Legilinguistics, 2017)
The heavy Foreign Direct Investment (FDI) in Tunisia which is in progress now will have its impact on the translation industry in the forthcoming years. But while most Tunisian translation teachers and professional translators agree on the urgent need to bridge the gap between the translation classroom and the real world of the translation market (the Academic and Professional Gap (APG)), academic traditions are inhibiting a clear critical focus on this APG. Teachers are still educating students in general skills and academic institutions do not try to frame appropriate strategies to train them to work in specific jobs. Therefore, such traditions are less likely to allow students to be able to succeed when they join this market, and to expect sound career development as they upgrade their skills. Translatorship is after all granted by the market and not by any academic institution. In the face of these challenges, this paper will draw attention to some of the available opportunities which are deemed of paramount importance in any attempt to achieve more professionally-oriented translation training. These opportunities will lead to some concrete and practical suggestions on how to aptly use corpora in the translation classroom, on the one hand, and how to profit from the translation experience inside the United Nations system, on the other.